Augmented Reality as a Learning Medium for Arabic Sentence Structures: Evidence from a Quasi-Experimental Study - Muhammad Nasrullah; Achmad Baihaqi; Ahmad Zubaidi; Jepri Nugrawiyati (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2025)
This study investigates the potential of Augmented Reality (AR) as a learning medium to improve students’ comprehension of Arabic sentence structures. Employing a quasi-experimental pretest–posttest control group design, the research involved 60 fourth-semester students of the Arabic education program, divided into experimental and control classes. Data were obtained from achievement tests and perception questionnaires. The findings showed that students in the AR class achieved significantly higher gains in syntactic comprehension than those in the control class, with a large effect size indicating the strong pedagogical impact of AR. In addition, students expressed highly positive attitudes toward AR, perceiving it as motivating, easy to use, and effective in visualizing grammatical structures. These results suggest that AR not only strengthens the cognitive processes of dual coding and spatial visualization but also contributes to the pedagogical development of Arabic language instruction. The study highlights the novelty of applying AR in Arabic syntax learning and offers theoretical implications for computer-assisted language learning and applied linguistics.